Forest of the Pygmies - Allende, Isabel; Peden, Margaret Sayers (New York : HarperTrophy, 2006)
Eighteen-year-old Alexander Cold and his grandmother travel to Africa on an elephant-led safari, but discover a corrupt world of poaching and slavery.
Translation of: Bosque de los Pigmeos.
Kliatt.
Library Media Connection.
Voice of Youth Advocates (V.O.Y.A.).
7.2
5-8
Keywords: Elephants -- Juvenile fiction; Grandmothers -- Juvenile fiction; Poaching -- Juvenile fiction; Adventure and adventurers -- Fiction; Elephants -- Fiction; Grandmothers -- Fiction; Poaching -- Fiction; Adventure fiction; Elephants -- Fiction; Grandmothers -- Fiction; Poaching -- Fiction; Kenya -- Juvenile fiction; Kenya -- Fiction; Kenya -- Fiction